ANTHROPOMETRIC INDICES MEZOPHARYNX SOFT PALATE AND CLEFT IN CHILDREN WITH ITS TO URANOSTAPHILOPLASTY - Kharkov, L.; Yakovenko, L.; Васьківська, М.О. (World of Medicine and Biology, 2016)
The aim was to assess the size of the soft palate length and volume mezofarynhsa and their relationships in children is normal, with congenital nonunion palate aged from 6 months to 3 years uranostafiloplastyky. Materials and Methods: 180 children treated at the clinic Department of Surgical Dentistry and Maxillofacial Surgery childhood, NMU. OOBogomolets (CST №7 m. Kyiv). Results by complications of treatment and their causes, the ways of prevention, thus improving the quality of care to such patients. Conclusions: The age of patients regardless of cleft palate increased deficit soft palate length by an average of 2.3 mm ± - compared to normal children. Width mezofarynhsa children with palate nonunion increases with age from 11 to 14 mm is almost the same as when isolated, and at cross defects, but the biggest difference to the numbers observed 1 year - 12 mm and 14 mm respectively.The ratio of length to width of the soft palate in children with mezofarynhsa palate nonunion in 2 times less than normal due to a wide mezofarynhsa. This requires an extension of the soft palate is almost 2 times to achieve effective retrotranspozytsiyi soft palate.